COMPORTAMIENTO CIRCADIANO DEL GASTERÓPODO NERITA SCABRICOSTA EN EL INTERMAREAL ROCOSO DE ISLA LA PALMA, PACÍFICO COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
We studied the circadian behavior during the foraging activity of the gastropod Nerita scabricosta at low tide. To measure the behavior we recorded the traveled distance and corresponding duration during foraging activity, according to the dial periods (day and night) in April 2010. Gastropods were measured and weighed after fiishing their activity. Finally, values of air temperature and humidity were recorded for each sampling time and dial period. The foraging activity by N. scabricosta did not vary signifiantly between day and night. However duration increased at night, period characterized by lower temperature and higher humidity. In addition, it was found that the activity was continuous, regardless the period.